Patterns of temporal lobe reaction and radiation necrosis after particle radiotherapy in patients with skull base chordoma and chondrosarcoma - a single-center experience - Mattke, Matthias; Ohlinger, Matteo Leon; Bougatf, Nina; Wolf, Robert; Welzel, Thomas; Roeder, Falk; Gerum, Sabine; Fussl, Christoph; Annon-Eberharter, Natalee; Ellerbrock, Malte; Jäkel, Oliver; Haberer, Thomas; et al. (Cancers, 2024)
BACKGROUND: The current study aims to evaluate the occurrence of temporal lobe reactions and identify possible risk factors for patients who underwent particle therapy of the skull base. - METHODS: 244 patients treated for skull base chordoma (n = 144) or chondrosarcoma (n = 100) at the Heidelberg Ion Beam Therapy Center (HIT) using a raster scan technique, were analyzed. Follow-up MRI-scans were matched with the initial planning images. Radiogenic reactions were contoured and analyzed based on volume and dose of treatment. - RESULTS: 51 patients with chordoma (35.4%) and 30 patients (30%) with chondrosarcoma experienced at least one temporal lobe reaction within the follow-up period (median 49 months for chondrosarcoma, 62 months for chordoma). Age, irradiated volume, and dose values were significant risk factors for the development of temporal lobe reactions with the highest significance for the value of DMax-7 being defined as the dose maximum in the temporal lobe minus the 7cc with the highest dose (p = 0.000000000019; OR 1.087). - CONCLUSION: Temporal lobe reactions are a common side effect after particle therapy of the skull base. We were able to develop a multivariate model, which predicted radiation reactions with a specificity of 99% and a sensitivity of 52.2%.